2005
DOI: 10.1161/01.atv.0000188554.49745.9e
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Endothelial Progenitor and Bone Marrow Cells Influences Atherosclerotic Plaque Size and Composition in Apolipoprotein E Knockout Mice

Abstract: Objectives-Recent clinical trials use cell therapy with bone marrow (BM) cells or endothelial progenitor cells (EPCs) for ischemic syndromes. We explored the effect of BM cell-or spleen cell-derived EPC transfer on plaque size and stability markers in the apolipoprotein E knockout (apoE KO) mouse model. Methods and Results-ApoE KO mice aged 10 weeks served as recipients. Labeled BM cells and spleen cell-derivedEPCs from age-matched apoE KO mice were injected intravenously to 2 groups of recipient mice each. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 36 publications
3
120
0
6
Order By: Relevance
“…In particular, it was shown recently that transplantation of bone marrow-derived MSC induced vascular remodeling and calcification after balloon angioplasty in hyperlipidemic rats [52]. Another previous study showed increased size of atherosclerotic lesion as a result of MSC homing [53]. Also severe intramyocardial calcification was observed after transplantation of unselected bone marrow cells after myocardial infarction [54].…”
Section: Discussionmentioning
confidence: 97%
“…In particular, it was shown recently that transplantation of bone marrow-derived MSC induced vascular remodeling and calcification after balloon angioplasty in hyperlipidemic rats [52]. Another previous study showed increased size of atherosclerotic lesion as a result of MSC homing [53]. Also severe intramyocardial calcification was observed after transplantation of unselected bone marrow cells after myocardial infarction [54].…”
Section: Discussionmentioning
confidence: 97%
“…6,13 Taking into account multiple macro-and microvascular complications of diabetes, we inquired a) whether transplantation of BMDCs may affect some of these functional abnormalities, and b) whether the competence of BMDCs in diabetic mice is preserved. Here, we report a dramatic improvement of macrovascular dysfunction and insulin sensitivity in db/db mice recipients of syngeneic BMDC isolated from the non-diabetic mice (but not from their diabetic counterparts), and provide evidence for BMDC incompetence in diabetic animals.…”
mentioning
confidence: 99%
“…The systemic application of healthy wild-type EPCs in atherosclerotic apolipoprotein E-knockout mice has been shown to improve endothelial function and to inhibit atherosclerotic lesion progression independent of high serum cholesterol levels [48] . However, these beneficial effects were not observed in a study conducted by George et al [49] in which aortic sinus lesion size was significantly increased in mice receiving EPCs compared with controls. Mice receiving EPCs showed plaques with larger lipid cores, thinner fibrous caps, and a higher number of infiltrating CD3 cells, suggesting an effect on plaque stability.…”
Section: Epcs and Endothelial Repairmentioning
confidence: 77%